Estruturação dos custos logísticos em uma operação de importação de uma carga conteinerizada - Silva, Pedro Henrique Monteiro da (2019)
Globalization has caused an expansion of global economies and foreign trade is one of the main agents of this phenomenon. So, the ports assumed a crucial and determining role for the national and regional economy. The national economy has also undergone this expansion, however, the country occupies only 55th position in the global logistics ranking. Problems in Brazil's infrastructure, tax burden and trade barriers are major obstacles to Brazil's economic development. The literature points to logistics costs as one of the main factors to be mitigated to improve a country position in the global competitive scenario. In this context, the research proposes to answer the following research question: how to structure the logistics costs of a containerized cargo shipped through a national port. For this, it was necessary to map the process of importing the prime granite cargo, identify the agents involved in the process, survey the activities and resources involved, structure the activity costing methodology (ABC) and, finally, segregate which activities generate logistics costs. Data collection was performed through the application of semi-structured interviews, previously validated. At the end of each interview and observation, a compilation and crossing of the data along with the document analysis was performed. With these, it was possible to survey the dictionary of activities and resources used in the process, steps that allowed the structuring of costs using the ABC methodology. Then the logistics costs were segregated by type: Supply, Plant and Distribution. By applying this methodology to one of the agents in the mapped chain, it was found that of the total costs incurred in its operation, 64.3% are of a logistical nature. Of the total logistics costs found, 61.3% are incurred in the supply logistics phase, 28.2% in the plant logistics phase and 10.5% in the distribution logistics phase.